Influence of individualized psychological intervention on nursing students in the practice of internship management (管理实习中个性化心理干预对实习护生的影响) - ZHOU Fengqin (周丰勤); WANG Weixian (王伟仙) (Association of Integrative Nursing, 2023)
Objective To explore the management countermeasures of nursing students' psychological problems in the middle and later period of internship practice, improve the psychological status of nursing students, stabilize the psychology of nursing students' practice, and improve their professional identity. Methods A total of 64 nursing students in the middle and later stages of their internship were selected as the research objects, and individualized psychological intervention was conducted according to the characteristics of each person in the management practice, and the intervention effect was evaluated by questionnaire survey before and after the management practice. Results After implementation of individualized psychological intervention, there were more students who had intention to become a nurse after graduation, and a decreased proportion of students with job burnout or anxiety status were observed at the end of internship practice compared with that at the beginning of internship, with a significant difference (P<0. 05). Conclusion In the internship management practice, paying attention to the individualized psychological intervention of nursing students can help them form a positive professional attitude, guarantee nursing safety and improve professional identity. (目的 探讨护生实习中后期心理问题的管理对策, 改善护生心理状况, 稳定护生实习心态, 提高护生职业认同感。方法 选取实习中后期的64名护生为研究对象, 在管理实习中根据每个人的特点进行个性化心理干预, 并在管理实习前和实习后采用问卷调查的方式对干预效果进行评价。结果 干预后护生的职业意愿较干预前提高提高, 存在职业倦怠、焦虑心理的护生人数占比较干预前降低, 差异有统计学意义(P＜0. 05)。结论 在管理实习中, 注重护生的个性化心理干预, 有助于帮助他们形成积极的职业态度, 保障护理安全, 提高职业认同感。)